A method using the cephalic vein for superdrainage in breast reconstruction. Issue 6 (22nd July 2019) - Tokumoto, Hideki; Akita, Shinsuke; Arai, Minami; Kubota, Yoshitaka; Kuriyama, Motone; Mitsukawa, Nobuyuki
Abstract: Background: In breast reconstruction, a superdrainage procedure using the superficial inferior epigastric vein has been described. The purpose of this study was to investigate whether the utility of cephalic vein (CV) was equivalent to that of serratus anterior muscle branch of the thoracodorsal vein (SA) and lateral thoracic vein (LTV) for recipient vein. Methods: Eighty‐eight patients were enrolled in this study. The superdrainage was not performed if the internal mammary vein diameter was greater than, or equal to, that of the deep inferior epigastric vein diameter. In superdrainage cases, the SA or LTV was used as the recipient vein firstly, and the CV was used when both of them were unsuitable. Results: The superdrainage was performed in 45 (51.1%) patients. No significant differences were observed between with and without superdrainage. In superdrainage group, the CV was used in 7 (15.5%) patients. In two groups (CV vs. LTV and SA), because we added to perform superdrainage to the CV at the time of re‐exploration and tried to use the SA or the LTV firstly, the re‐exploration rate (28.6 vs. 0%) and operating time (652.1 vs. 591.1 min) of CV group were significantly high ( p = .023 and .028). No complications were observed, due to CV harvesting. Other characteristics showed no significant differences. Conclusions: At the point of superdrainage, the CV was equivalent to the SA and LTV. Using of the CV would only be essential in rare cases; nonetheless, the possibility of its use should be considered.